The Business of Plant Breeding: Market led Approaches to Plant Variety Design in Africa - Persley, Gabrielle (CABI, 2017)
This book is the result of a study on demand-led plant variety design for changing markets in Africa, the purpose of which is to identify and share best practices in demand-led plant breeding from private and public sector breeding programmes worldwide. The intended audiences are professionals in plant breeding and related areas, such as seed production, who have interests in developing and disseminating new plant varieties as a way to increase productivity and profitability in crop agriculture, especially in Africa. The volume is also intended for use as a resource book for the education of postgraduate scholars in plant breeding and genetics, and for the continuing professional development of plant breeders. For this purpose, boxes are included in the main sections of each chapter that summarize its educational objectives and present the key messages and questions that are involved; in addition, there is a final box at the end of each chapter that summarizes its overall learning objectives.